Character Building Values in Student Teacher’s Lesson Plans: A Content Analysis - Farhana Nurhayya; Ellis Tamela (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
Character-building which has become one of the major concerns in the Indonesian national educational system should be addressed by the education stakeholders in various ways, one of which is via academic documents such as curriculum, syllabus, and lesson plan. Many researchers have conducted studies regarding character-building values that are revealed in EFL teacher's lesson plans. However, they have not addressed character-building values in student teacher's lesson plans. This study aimed to investigate character-building values in student teacher’s lesson plans using content analysis. Five lesson plans designed by 15 student teachers were analyzed based on character-building values by the Ministry of Education and Culture. The findings showed that 5 character-building values were inserted in the student teacher's lesson plans such as being religious, hard work, responsible, collaborative, and communicative. The most frequent character-building values were being communicative, while the less frequent character-building values were being religious.